Neoadjuvant chemotherapy in technically unresectable carcinoma of external auditory canal - Joshi, Amit; Tandon, Nidhi; Noronha, Vanita; Dhumal, Sachin; Patil, Vijay; Arya, Supreeta; Juvekar, Shashikant; Agarwal, Jaiprakash; DCruz, Anil; Pai, Prathmesh; Prabhash, Kumar (Indian journal of medical and paediatric oncology, 2015)
Abstract Background: Carcinoma of external auditory canal (EAC) is a very rare malignancy with surgical resection as the main modality of treatment. The outcomes with nonsurgical modalities are very dismal. We present a retrospective analysis of 4 patients evaluating the role of neoadjuvant chemotherapy in technically unresectable cancers. Materials and Methods: This is a retrospective analysis of 4 patients from our institute from 2010 to 2014 with carcinoma EAC who were deemed unfit for surgery due to extensive disease involving occipital bone with soft tissue infiltration ( n = 2), temporal dura ( n = 1), left temporal lobe, and extensive soft tissue involvement ( n = 1). All these patients received neoadjuvant chemotherapy with docetaxel, cisplatin and 5 fluorouracil ( n = 3) and paclitaxel and cisplatin ( n = 1). Results: Response evaluation showed a partial response (PR) in 3 and stable disease (SD) in 1 patient by Response Evaluation Criteria in Solid Tumors criteria. All 3 patients who received 3 drug chemotherapy had PR while 1 patient who received 2 drug chemotherapy had SD. Two of these patients underwent surgery, and other 2 underwent definitive chemoradiation. One of 3 patients who achieved PR underwent surgical resection; the other 2 remained unresectable in view of the persistent intradural extension and infratemporal fossa involvement. One patient who had SD could undergo surgery in view of clearance of infraatemporal fossa. Recent follow-up shows that 3 out of these 4 patients are alive. Conclusion: This indicates that there may be a role of induction chemotherapy in converting potentially unresectable tumors to resectable disease that could produce better outcomes in carcinoma EAC.